Nursing care for patients who had strokes - Marciniak, Magdalena; Królikowska, Agnieszka; Ślusarz, Robert; Jabłońska, Renata; Książkiewicz, Barbara (Nursing Problems / Problemy Pielęgniarstwa, 2010)
The aim of this work is to show contemporary concepts concerning the proper care, rehabilitation as well as health education of patients who had strokes and for their families. All nursing and rehabilitation activities, presented in this work, are aimed at increasing patients’ chances of survival, achieving better physical fitness and self-reliance. This work was based on researches survey and available literature. The verification of collected material helped the authors to assess the degree of knowledge concerning strokes of healthy patients as well as preparation of stroke patients to selfcare. Moreover, this work includes issues concerning health education. Widely propagated educational activities could help the patient to overcome fear and could help to take a positive attitude towards the illness and his own. Nursing Topics 2010; 1 (1): 83-88